Emerging Organic Surface Chemistry for Si Anodes in Lithium-Ion Batteries: Advances, Prospects, and Beyond - Chen, Zidong; Soltani, Askar; Chen, Yungui; Zhang, Qiaobao; Davoodi, Ali; Hosseinpour, Saman; Peukert, Wolfgang; Liu, Wei (Advanced Energy Materials, 2022)
Due to its uniquely high specific capacity and natural abundance, silicon (Si) anode for lithium-ion batteries (LIBs) has reaped intensive research from both academic and industrial sectors. This review discusses the ongoing efforts in tailoring Si particle surfaces to minimize the cycle-induced changes to the integral structure of particles or electrodes. As an upgrade or alternative to conventional coatings (e.g., carbons), the emerging organic moieties on Si offer new avenues toward tuning the interactions with various battery components that are key to electrochemical performances. The recent progress on understanding Si surfaces is reviewed with an emphasis on newly emerged diagnostic tools, which increasingly points to the critical role of organic components in stabilizing Si. The detailed analysis on the chemistry-structure-performance relationships in Si surface are discussed and the successful cases demonstrating the functions of the organic layers are provided, that is, via tailored interactions toward electrolyte or binder or conductive agents, are recapped. Various synthetic strategies for designing the surface organic layers are discussed and compared, highlighting the versatility and tunability of surface organic chemistry. The holistic considerations and promising research directions are summarized, shedding light on in-depth understanding and engineering Si surface chemistry toward practical LIBs application.
CRIS-Team WoS Importer:2022-07-29